The persecution of the Jews and Muslims of Portugal : King Manuel I and the end of religious tolerance (1496-7) - Soyer, François (Medieval Mediterranean, 2007)
In 1496-7, King Manuel I of Portugal forced the Jews of his kingdom to convert to Christianity and expelled all his Muslim subjects. This book pieces together the developments that led to the events of 1496-7 and presents a detailed reconstruction of the persecution itself.